Physically stimulus-responsive nanoparticles for therapy and diagnosis - Farjadian, Fatemeh; Ghasemi, Soheila; Akbarian, Mohsen; Hoseini-Ghahfarokhi, Mojtaba; Moghoofei, Mohsen; Doroudian, Mohammad (Frontiers in Chemistry, 2022)
Nanoparticles offer numerous advantages in various fields of science, particularly in medicine. Over recent years, the use of nanoparticles in disease diagnosis and treatments has increased dramatically through the development of stimuli-responsive nanosystems, which can respond to internal or external stimuli. In the last ten years, many preclinical studies were performed on physically triggered nanosystems to develop and optimize stable, precise, and selective therapeutic or diagnostic agents. In this regard, the systems must meet the requirements of efficacy, toxicity, pharmacokinetics, and safety before clinical investigation. Several undesired aspects need to be addressed to successfully translate these physical stimuli-responsive nano-systems, as biomaterials, into clinical practice. These have to be commonly taken into account when developing physically triggered systems; thus, also applicable for nano-systems based on nanomaterials. This review focuses on physically-triggered nano-systems (PTNS) with diagnostic or therapeutic and theranostic applications. Several types of physically triggered nano systems based on polymeric micelles and hydrogels, mesoporous silica, and magnets are reviewed and discussed in various aspects.